The impact of quantitative methods on equity mutual funds' performance - Fernandes, David Matias (2019)
In this study, we analyze the impact of using quantitative methods in fund management on the performance of equity mutual funds using a sample of US mutual funds in the 2000-2015 period. Our results show that quantitative funds tend to underperform when compared to non-quantitative funds. We also show that fund size decreases more the performance of quantitative funds, while fund family size penalizes more the performance of these funds. Regarding the effect of 2007-2008 crisis on the performance of quantitative equity mutual funds, we do not find statically significant differences between quantitative and non-quantitative funds.